2022
DOI: 10.31635/ccschem.021.202101056
|View full text |Cite
|
Sign up to set email alerts
|

Nitrene-Mediated P–N Coupling Under Iron Catalysis

Abstract: P-N and P=N bonds play important roles in the design and synthesis of functional molecules such as bioactive compounds and organic ligands for catalysis. Existing methods for P-N coupling mostly rely on Staudinger condensation or nucleophilic substitution between phosphorus electrophiles and amine nucleophiles. Herein, we report a nitrene-mediated intermolecular P-N coupling reaction between various phosphorus nucleophiles and dioxazolones under simple iron-catalyzed conditions. These reactions offer an effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Based on the aforementioned observations and previous literature reports, a plausible mechanism is proposed in Scheme . The FeCl 3 -mediated hydrogenation would be initiated by the cleavage of the N -Boc group under assistance of FeCl 3 and heating, affording diazene species A .…”
Section: Resultsmentioning
confidence: 97%
“…Based on the aforementioned observations and previous literature reports, a plausible mechanism is proposed in Scheme . The FeCl 3 -mediated hydrogenation would be initiated by the cleavage of the N -Boc group under assistance of FeCl 3 and heating, affording diazene species A .…”
Section: Resultsmentioning
confidence: 97%
“…The presence of P t Bu 3 ligand significantly accelerated the formation of 3 a and the reaction can be completed within 10 minutes (entry 3). Interestingly, our previous studies showed that P t Bu 3 alone could undergo rapid P ‐amidation with 1 to give N ‐acyl iminophosphorane 4 in high yield under similar FeCl 2 ‐catalyzed conditions at rt [15a] . However, the formation of 4 was mostly suppressed (<1 %) in the N ‐amidation of aniline 2 with 1 using 20 mol % of P t Bu 3 as a ligand, suggesting the role of P t Bu 3 has changed in the presence of 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Functionalities such as sulfide (7), carboxylic acid (8), and sulfanilamide (9) were well tolerated. Substrates containing heterocycle motifs such as dioxane (15), thiazole (17), and coumarin (18) worked well. Aniline-based drug molecules like sulfamethoxazole (14, antibiotic) and lenalidomide (19, anticancer) reacted smoothly with 1 to give the corresponding products in moderate to good yields.…”
Section: Substrate Scope Of the Hydrazide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the S -amidation of sulfur, the utility of dioxazolones as acyl nitrene precursors have also been demonstrated in other important transformations such as C–H amidation reactions in recent years 66 73 . We previously showed that dioxazolones can enable efficient amidation of arylamines and various phosphorus compounds to construct N–N and P–N bonds under the catalysis of iridium or iron 74 , 75 . Motivated by the prevalence of thiol group in both small molecules and peptides, we questioned whether dioxazolones can react with SH to give the sulfenamide product under proper metal-catalyzed conditions.…”
Section: Resultsmentioning
confidence: 99%